The Formation and Evaluation of the Faulted Topography in the Burdur Basin, Lakes Region, SW Anatolia - Atalay, Ibrahim; Altunbas, Sevda; Siler, Muzaffer (Istanbul Univ, Fac Letters, Dept Geography, 2020)
The Burdur Basin, which is located in the Lakes Region in SW Anatolia, was formed by vertical faulting movements. The erosion surfaces were developed on the marl deposit in accordance with the lowering of the base level in each faulting movement in the east of the Burdur Basin. These erosion surfaces are at an elevation of 980, 995, 1040, 1115, 1200, 1300-1340 m on the Neogene marl deposit and knickpoints along the valleys indicate six times depressed along the fault lines of the Burdur Basin. The fault scarp extending on the east of the Burdur Basin was dissected deeply as a triangular facet; the accumulation of materials that had been transported from the highlands led to the formation of dejection fans, cones and re-deposited marl deposit in the eastern part of the Lake Burdur Basin. Earthquakes have occurred frequently since historical times and the subsidence that has taken place in the deeper part of Lake Burdur has attained a depth of more than 70 m in the southern part of the lake which may indicate continued tectonic activity. Lake Burdur, which is the remnant of Neogene Lake, containing some heavy minerals supports the life of only one species of fish and poor flora and fauna.
Keywords: Faulted structure; erosion surface; Burdur-Golhisar Basin